MALT1 protease function in regulatory T cells induces MYC activity to promote mitochondrial function and cellular expansion. Issue 1 (2nd November 2021) - Rosenbaum, Marc; Schnalzger, Theresa; Engleitner, Thomas; Weiß, Christin; Mishra, Ritu; Mibus, Cora; Mitterer, Theresa; Rad, Roland; Ruland, Jürgen
ABSTRACT: Regulatory T cells (Tregs) are essential for the inhibition of immunity and the maintenance of tissue homeostasis. Signals from the T‐cell antigen receptor (TCR) are critical for early Treg development, their expansion, and inhibitory activity. Although TCR‐engaged activation of the paracaspase MALT1 is important for these Treg activities, the MALT1 effector pathways in Tregs remain ill‐defined. Here, we demonstrate that MALT1 protease activity controls the TCR‐induced upregulation of the transcription factor MYC and the subsequent expression of MYC target genes in Tregs. These mechanisms are important for Treg‐intrinsic mitochondrial function, optimal respiratory capacity, and homeostatic Treg proliferation. Consistently, conditional deletion of Myc in Tregs results similar to MALT1 inactivation in a lethal autoimmune inflammatory syndrome. Together, these results identify a MALT1 protease‐mediated link between TCR signaling in Tregs and MYC control that coordinates metabolism and Treg expansion for the maintenance of immune homeostasis. Abstract : In murine CD4 + Foxp3 + regulatory T cells (Tregs), T‐cell receptor (TCR)/CD28‐induced MALT1 protease activity promotes MYC and MYC‐controlled gene expression in a c‐Rel‐dependent manner. This MALT1‐MYC axis drives mitochondrial metabolism and the respiratory capacity of Tregs, which is critical for Treg proliferation and the maintenance of immune homeostasis.